Response of black mulberry onto white mulberry rootstock to stenting (cutting-grafting) techniques and IBA concentrations - Solgi, Mousa; Taghizadeh, Mina; Bagheri, Hossein (Ornamental Horticulture, 2021)
Ornamental black mulberry (Morus nigra L.) is used in landscape. Ornamental black mulberry which has high shade, tolerates air pollution and wind. White mulberry (Morus alba L.) is proper for kind of soils conditions. Therefore, this research was conducted to investigate the effects of stenting methods and IBA levels on some characters of black mulberry scions onto white mulberry rootstock for the first time. For this purpose, an experiment was carried out as factorial in completely randomized design with 10 replications. Two factors were including two stenting method (splice and omega) and three levels of Indole-3-butyric acid (0, 500 and 1000 mg L-1). Three months after grafting, percentage of rootstock callus formation, percentage of rooting, percentage of leaf formation, number of leaf formation, the longest shoot and the longest root formation were measured. Results showed that the effect of stenting method was significant on all of evaluated parameters and splice method was superior to omega method. Also, the effects of different levels of IBA were significant on all of measured traits and they are increased by increasing the levels of IBA and the best was with 1000 mg L-1. The interaction effects of these factors are significant on all of measured characteristics except for percentage of rootstock callus formation and rooting percentage. In conclusion, the stenting via splice method had higher success in comparison with omega method and the morphological traits increased by increasing the application of higher levels of IBA. The application of stenting method by splice plus 1000 mg L-1 IBA which was carried out for the first time is recommended for reproduction of ornamental black mulberry onto white mulberry.